2008
DOI: 10.1007/s10584-008-9476-z
|View full text |Cite
|
Sign up to set email alerts
|

A history of ENSO events since A.D. 1525: implications for future climate change

Abstract: Reconstructions of past climate are important for providing a historical context for evaluating the nature of 20th century climate change. Here, a number of percentile-based palaeoclimate reconstructions were used to isolate signals of both phases of El Niño-Southern Oscillation (ENSO). A total of 92 (82) El Niño (La Niña) events were reconstructed since A.D. 1525. Significantly, we introduce the most comprehensive La Niña event record compiled to date. This annual record of ENSO events can now be used for ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
241
2
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(273 citation statements)
references
References 87 publications
(127 reference statements)
22
241
2
8
Order By: Relevance
“…Although the relation between climate change and El Niño events has been debated during the last decades [27][28][29][30][31][32], recent research has revealed that 43% of extreme El Niño events have occurred since the start of the 20th century and 30% during the post-1940 period [33]. These results suggest that ENSO may operate differently under natural (pre-industrial) and anthropogenic background states [33]. The aim of this study is to investigate the evolution of coping strategies developed by the Peruvian anchovy fishery to deal with environmental variability and extreme El Niño events, whose frequency can be expected to increase under current climate change scenarios [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Although the relation between climate change and El Niño events has been debated during the last decades [27][28][29][30][31][32], recent research has revealed that 43% of extreme El Niño events have occurred since the start of the 20th century and 30% during the post-1940 period [33]. These results suggest that ENSO may operate differently under natural (pre-industrial) and anthropogenic background states [33]. The aim of this study is to investigate the evolution of coping strategies developed by the Peruvian anchovy fishery to deal with environmental variability and extreme El Niño events, whose frequency can be expected to increase under current climate change scenarios [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these differences, documentary sources often have fewer dating uncertainties associated with them than proxy records, so provide a good source of comparison for the logbook-based reconstructions as their dating errors are also minimal. Finally, Gergis and Fowler (2009), GF09, present a chronology of ENSO events since AD 1525, the same period as the Quinn chronology, which looked at both El Niño and La Niña events. They used a range of complementary proxy data and documentary evidence.…”
Section: Documentary Enso Reconstructionsmentioning
confidence: 99%
“…Finally, a comparison to the reconstructions of Gergis and Fowler (2009) was carried out. GF09 identify seven moderate to extreme El Niño and seven moderate to extreme La Niña events in the period 1815-1854.…”
Section: Combined Multi-proxy and Documentary 1815/16-1853/54mentioning
confidence: 99%
“…Mature A. marina trees in New Zealand range in size from <1 m to over 6 m with taller trees generally found toward the northern distribution range (Morrisey et al, 2010). Mangrove expansion has been associated with increased sedimentation and periods of favorable weather conditions (low wind and wave activity) occurring during El Niño weather patterns, which are predicted to strengthen with climate change (Cane, 2005;Gergis and Fowler, 2009;Morrisey et al, 2010).…”
Section: Study Sitesmentioning
confidence: 99%